Emerging immunotherapy and tumor microenvironment for advanced sarcoma: a comprehensive review - Huang, Hai; Fan, Yiwei; Zhang, Shuling; Bai, Xueli; Wang, Xiaonan; Shan, Fengping (Frontiers in Immunology, 2025)
Sarcomas are heterogeneous mesenchymal malignancies classified as soft-tissue sarcomas (STS) and bone sarcomas. Advanced cases respond poorly to standard therapies, highlighting the need for novel strategies. Immunotherapies, including PD-1/PD-L1 inhibitors, adoptive cellular therapies, vaccines, and oncolytic viruses, have shown promise in specific sarcoma subtypes. This review explores these approaches, emphasizing the prognostic significance of immune cells within the tumor microenvironment (TME), such as tumor-associated macrophages (TAMs) and tumor-infiltrating lymphocytes (TILs), and their correlation with clinical outcomes. We also discuss challenges in immunotherapy efficacy, the importance of biomarker-driven personalized therapies, and the potential of a combination regimen with chemotherapy, radiation, and cytokine agents. Overall, this review highlights the evolving role of immunotherapy in advanced sarcomas, the critical influence of the TME, and the need to optimize synergistic treatment approaches to enhance patient outcomes.